Efficient Biginelli Synthesis of 2-Aminodihydropyrimidines under Microwave Irradiation - Felluga, Fulvia; Benedetti, Fabio; Berti, Federico; Drioli, Sara; Regini, Giorgia (Synlett, 2018)
A practical and general method for the Biginelli cyclocondensation of guanidine with aldehydes and β-dicarbonyl compounds is described and illustrated with the synthesis of a set of 26 functionalized 2-amino-3,4-dihydropyrimidines. The simple protocol involves the microwave-mediated reaction of a twofold excess of guanidine hydrochloride with the required reaction partners in an alcohol at 120 °C. Yields are generally good, with short reaction times and a simple workup. The scope is considerably wider than that of similar reactions carried out under conventional heating.
Keywords: Biginelli reaction; microwave heating; guanidine; dicarbonyl compounds; aminodihydropyrimidines; multicomponent reactions